SKILL DEVELOPMENT TRAINING MODEL Slalom Dribbling and Pass Techniques in Football (Research Development at the Athlete's Son Intermediate School Football (SSB) in Banda Aceh) - Irfandi Irfandi; Sugiyanto Sugiyanto; Muchsin Doewes (JOURNAL OF EDUCATION SCIENCE, 2015)
That background for this research is the ability in mastering the technical skills led mainly led slalom and pass in football where before conducting research there are a number of athletes who do not really optimal in mastering the technical skills, this has happened to the son of middle-level athletes in the School of Football (SSB ) in Banda Aceh. This study aims to developt a wide range of draft model design engineering skills training, preparing in the manufacture of the initial product, carry out test small group, large group test, and implement test the effectiveness of the product, so as to obtain results in the form of improved quality of training and technical mastery of athletes, especially herding slalom and pass the football at the middle school level athletes sons Football (SSB) in Banda Aceh.Research development or better known as the research and development carried out at the School of Football (SSB) Real Madrid Foundation RMF-Aceh, and the School of Football (SSB) Young Stars Banda Aceh. The subjects of the study is the son of middle-level athletes who numbered 44 athletes from SSB Real Madrid Foundation, and 22 athletes from Young Stars SSB Banda Aceh. Test phase was conducted in a small group of Young Stars SSB, followed by a large group test conducted in SSB Real Madrid Foundation Aceh. While the implementation phase of product effectiveness test conducted in SSB Real Madrid Foundation and the Young Stars SSB.This study was able to develop the skills training model figure terutamamodel herding techniques slalom skills training and pass the intermediate level athletes sons School Football (SSB) in Banda Aceh. Results mastery of skills training models herding techniques and pass the slalom obtained based on: 1) Summary data of the percentage of questionnaires and validation by a number of experts who obtained an average score of 67% and 73%, and it was included in the category of pretty valid, means that the product model of skill training and pass the slalom herding techniques in football can be used and applied as a model practice guidelines on SSB son of middle-level athletes. Percentage data model results in ujicobakan in small groups derived from mastery of technical skills training model of the athletes which amounted to 81.10%, which means that a valid use, and a large group gained mastery of skills training models herding techniques slalom and pass in football is at 85.34 % means that the product is valid to use, so it can be interpreted as if the models developed in real capable of delivering results, and a very remarkable contribution accurate, especially in the mastery of technical skills training models led slalom and pass in football.Thus, to interpret the results of the development of a model for a given treatment group, in which case there is a significant difference between the groups before being given treatment when compared with the group after being given treatment. Based on data from the pretest-posttest athlete shows some results of technical mastery skills training models amounted to 62.27%, and thereafter the product models (the process of treatment) then the effect of increased very significantly to the mastery of technical skills training model products to get the results of 67.27%. Differences in the form of percentage figures is a result of the result of the provision and application of product models (such as treatment), where the impact of a given product models and demonstrate a very significant effect on the deeper levels, in terms of mastery of product models mainly herding engineering skills training models slalom and pass in football.Keywords: model design exercise, soccer, herding slalom, pass, treatment, and research development